Pengaruh Iradiasi Sinar Gamma pada Pertumbuhan Kalus dan Keragaman Planlet Tanaman Nilam - Abdul Kadir; Surjono H Sutjahjo; Gustav A Wattimena; Ika Mariska (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2007)
The Effect of Gamma Irradiation on Calli Growth andPatchouly Planlet Variation. Abdul Kadir, Surjono H.Sutjahjo, Gustav A. Wattimena, and Ika Mariska. Thisresearch was objected to study the effect of gamma irradiationon growth of calli and plantlet and phenotypic variationof patchouly plantlet. Research was conducted at the TissueCulture Laboratory of Center for Agricultural Biotechnologyand Genetic Resources Research and Development, Bogor.Gamma irradiation treatment was done at the Centre for Researchand Development of Isotop and Radiation Technology,BATAN, Jakarta. The treatment consisted of 5 level ofirradiation i.e. 0 (control), 5, 10, 15, and 20 Gy of gamma irradiation.The result showed that gamma irradiation of 20 Gydecrease calli quality index and increased percentage ofcalli death and inhibited calli growth at 30, 60 and 90 daysafter irradiation, also decrese number of shoots. Gamma irradiationof 5 Gy and 10 Gy increased growth planletcompared 15 Gy and 20 Gy, meanwhile gamma irradiation at20 Gy induced high frequency of phenotypic variation ofpatchouly plantlet.